PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI TEKS PROSEDUR SISWA KELAS IV SEKOLAH DASAR - Ni Komang Ayu Sri Apriani; Ni Made Ignityas Prima Astuti; Ni Putu Juni Artini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop Canva-based video learning media for procedural texts for elementary school students. The research method used in this study is Research and Development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of validators, material experts, and media experts, who assessed the feasibility of the developed learning media. Data collection techniques were conducted through interviews and validation sheets provided to the material and media experts to determine the level of feasibility of the learning media. The validation results showed that the developed learning media received 87.5% approval from the material experts and 88.39% approval from the media experts, categorized as very valid. These results indicate that the Canva-based video learning media is suitable for use as a learning medium in the learning process. This media is designed with an attractive appearance, systematic presentation of material, and easy-to-understand language, thus helping students understand procedural texts. Therefore, Canva-based video learning media can be used as an alternative learning medium to support the learning process in elementary schools.